Entrepreneurship and institutional change in post-socialist rural areas: Some evidence from Russia und the Ukraine - Christos Kalantaridis; Lois Labrianidis; Ivaylo Vassilev (Journal for East European Management Studies, 2007)
Are entrepreneurs in rural areas of Russia and the Ukraine any different from their urban based counterparts? What are the implications of the distinctiveness of rural entrepreneurship upon the institutional setting - given the weakness of the State? We focus upon the experience of rural areas of Novosibirsk and the Republic of Bashkortostan in Russia and Transcarpathia in the Ukraine. We argue that whilst in urban settings the advancement of post-socialist transformation resulted in increased diversity in the type of individual engaged in entrepreneurship. This raises concerns about the pace and direction of change in rural areas. However, even within the three localities under investigation there appears to be a growing divergence in the pathways of change. – – Unterscheiden sich Unternehmer in ländlichen Gebieten Russlands und der Ukraine von ihren städtischen Kollegen? Was sind die Folgen der Besonderheit von ländlichem Unternehmertum auf die institutionellen Rahmenbedingungen - vor dem Hintergrund des schwachen Staates? Dabei konzentrieren wir uns auf die ländlichen Gebiete von Nowosibirsk und der Republik Baschkortostan in Russland sowie Transkarpatien in der Ukraine. Wir behaupten, dass der Fortschritt der postsozialistischen Transformation lediglich im städtischen Umfeld zu einer verstärkten Vielfalt von individuellem Engagement im Unternehmertum geführt hat, nicht aber auf dem Lande. Dies verweist auf die Problematik des Tempos und der Richtung der Veränderungen in ländlichen Gebieten. Allerdings bestehen auch zwischen den drei Regionen wachsende Unterschiede bezüglich der eingeschlagenen Wandlungspfade.
Keywords: 650; entrepreneurs; institutions; rural areas; post-socialist transformation